Development of Ethnoscience-Based Teaching Materials to Improve Students' Scientific Literacy - Lovy Herayanti; Fuaddunnazmi Fuaddunnazmi; Baiq Azmi Sukroyanti (Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This research aims to produce a product in the form of an ethnoscience-based learning tool to improve the scientific literacy of prospective physics teachers that is valid and effective. The products developed are Student Worksheets (LKMs), teaching materials, and test instruments. This study used the research and development with the 4D model which consists of Define, Design, Develop and Disseminate. Data collection techniques used validation sheets and evaluation tools. The validity of the device data was analyzed using a Likert scale. The validity of the product was assessed by three expert validators. Assessment by validators with valid to very valid criteria. The effectiveness of the teaching materials developed by the researcher can be seen through the improvement of students' scientific literacy based on the results of the N-Gain test after being given a pretest and posttest. The results of this study indicate that the integration of ethnoscience-based teaching materials has a positive impact on improving students' scientific literacy in physics learning. The average pre-test score of 70.48 describes the students' initial understanding before ethnoscience-based learning. After participating in the learning, the average score increased to 83.33 on the post-test, which indicates that the material adapted to the local culture helps in understanding physics concepts more deeply. In addition to the increase in the average score, the N-gain score of 37.56% shows the effectiveness of ethnoscience-based learning in improving scientific literacy at a fairly significant level. This shows that, although there is still room for improvement, this approach has succeeded in increasing students' understanding of physics through the integration of cultural aspects.